N-type doping of black phosphorus single crystal by tellurium. (20th May 2020) - Yu, Ying; Xing, Boran; Yao, Jiadong; Niu, Xinyue; Liu, Yali; Wu, Xiaoxiang; Yan, Xiaoyuan; Li, Mengge; Sha, Jian; Wang, Yewu
Abstract: Black phosphorus has many potential applications in optoelectronic devices because of its unique properties. Adjusting its performance by doping is an important issue of research. In this paper, we synthesized high-quality Te-doped crystals by the chemical vapor transport method. Tellurium doping with an atomic ratio of 0.1% was confirmed by X-ray photoelectron spectroscopy, X-ray diffraction, and energy dispersive X-ray analysis. The performance of field effect transistors devices shows that the hole mobility of Te-doped black phosphorous (BP) is significantly improved compared with that of undoped-BP. The highest hole mobility at room temperature is 719 cm 2 V −1 s −1, and the electron mobility is 63 cm 2 V −1 s −1 . Te-doped BP field effect transistors show an obvious bipolar behavior.